2021
DOI: 10.1186/s12913-021-06821-6
|View full text |Cite
|
Sign up to set email alerts
|

Service providers’ perceptions of support needs for Indigenous cancer patients in Saskatchewan: a needs assessment

Abstract: Background In Saskatchewan, Canada, Indigenous cancer care services at the municipal, provincial, and federal levels are intended to improve quality care but can result in a complex, fragmented, and multi-jurisdictional health care system. A multi-phase needs assessment project was initiated to document Indigenous cancer care needs. Guided by Indigenous patient partners, clinicians, academics, and policy makers, the present study reflects a needs assessment of Indigenous cancer supports from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Two studies 18,19 focused on patient navigation in indigenous populations in Canada. Various barriers to care were reported, including finances, transportation, distance from service providers, language barriers, lack of indigenous representation in the health care system, and lack of culturally safe care, with ongoing perceptions of paternalism in current health care models 18,19 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies 18,19 focused on patient navigation in indigenous populations in Canada. Various barriers to care were reported, including finances, transportation, distance from service providers, language barriers, lack of indigenous representation in the health care system, and lack of culturally safe care, with ongoing perceptions of paternalism in current health care models 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Various barriers to care were reported, including finances, transportation, distance from service providers, language barriers, lack of indigenous representation in the health care system, and lack of culturally safe care, with ongoing perceptions of paternalism in current health care models. 18,19 Furthermore, distance and extended travel times were more than just a risk factor for delayed diagnosis and treatment because they represented a loss of income, extended isolation from community and family, as well as an interruption in the grief process. 18,19 Participants suggested that indigenous navigators could potentially offer better culturally tailored support, linguistically tailored resources, and promote patientprovider trust.…”
Section: Indigenous Populationsmentioning
confidence: 99%
See 3 more Smart Citations